Introducing heat-not-burn tobacco improves hematocrit and cigarette smoking-related symptoms in patients with smokers’ polycythemia and polycythemia vera - Kazuhide Iizuka; Yoshikazu Iizuka; Shun Ito; Toshihide Endo; Hironao Nukariya; Yuichi Takeuchi; Takashi Koike; Kazuya Kurihara; Hiromichi Takahashi; Masaru Nakagawa; Takashi Hamada; Shimon Ohtake; et al. (PLoS ONE, 2025)
Cigarette smoking induces relative and absolute erythrocytosis (smokers’ polycythemia). In patients with smokers’ polycythemia complicated by chronic obstructive pulmonary disease, the incidence and mortality rate of pulmonary embolism increase. Therefore, improving erythrocytosis by smoking cessation is important; however, smoking cessation is often difficult to achieve. This study investigated the influence of introducing heat-not-burn tobacco in patients with smokers’ polycythemia. Fifteen smokers with erythrocytosis were diagnosed with smokers’ polycythemia (n = 13) or polycythemia vera (n = 2) groups. The patients selected a switch to heat-not-burn (HNB) tobacco or smoking cessation, and the subsequent changes in hematological data and symptoms were evaluated. Eight patients with smokers’ polycythemia and two with polycythemia vera selected a switch to HNB tobacco, and the other five patients with smokers’ polycythemia selected smoking cessation. In both the HNB tobacco and smoking cessation groups, all patients showed improved hematocrit (Hct) and sputum volume and ameliorated numbness, headache, and vertigo. In the patients with smokers’ polycythemia, Hct of the HNB tobacco group was equivalent to that in the patients with smoking cessation group (47.51 ± 3.48% vs. 45.63 ± 2.79%, P = 0.605). Introduction of HNB tobacco may be useful for reducing erythrocytosis in smokers for whom smoking cessation is difficult.